Enhancing Students’ Understanding of Integrated Social and Natural Sciences through Experimental Learning at MIS Raudhatul Jannah - Julia Ekawati; Lukman Munir (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to enhance students’ understanding of Integrated Social and Natural Sciences (IPAS) through experimental learning at MIS Raudhatul Jannah. The research focuses on improving the quality of science education by introducing hands-on, interactive, and inquiry-based activities to engage students actively in learning processes. Traditional teaching methods in IPAS often lack student involvement, leading to passive learning and limited understanding of key scientific concepts. Therefore, this study seeks to implement experimental learning as a means to foster deeper understanding and encourage critical thinking among students. The research was conducted in two cycles with 30 students aged 9-12 years. The experimental learning activities included simple, hands-on experiments, demonstrations, and fieldwork to illustrate key concepts from both social and natural sciences. Data were collected through observations, pre- and post-tests, and student interviews to assess their understanding and engagement during the activities. The results showed a significant improvement in students’ ability to apply scientific concepts, perform experiments, and explain phenomena. Furthermore, students demonstrated increased enthusiasm and participation during the experimental sessions, which were reflected in their academic performance. This study concludes that experimental learning is an effective approach to enhance students’ understanding of IPAS. By engaging students in practical and interactive experiences, they develop a more comprehensive understanding of scientific principles, while also enhancing their problem-solving and critical thinking skills. It is recommended that MIS Raudhatul Jannah and similar institutions integrate more experimental learning opportunities into the curriculum to foster deeper learning and curiosity in students.